Emerging from the shadows? Perceptions, problems and potential consensus on the functional and civic roles of public affairs practice. (January 2016) - Davidson, Scott; Rowe, Oliver
In the context of public concern and negative media portrayals in regard to the civic impact of the public relations specialism of public affairs and lobbying, this article seeks to theorise normative roles in democracies alongside benchmarking the self-perception of practitioners against those of opinion forming elites. The article also explores how practitioners interpret their roles and locates a consensus in regard to their functional and civic contributions. A potential research agenda for testing the validity of these claims of a positive civic contribution is discussed. The article analyses the results of quantitative surveys of a representative sample of British members of parliament, and 722 UK opinion formers, plus 260 interviews with opinion formers in Washington DC. The results were complemented by a Delphi survey of UK public affairs practitioners that sought to identify and test areas of consensus in regard to both organisational and civic functions. The research finds that lobbying is perceived as legitimate by elites, but there are concerns over the quality of the information subsidy that is provided. Practitioners share an understanding with the public relations literature of their functional roles, and believe they make a social contribution by assisting policy-making, connecting society to politicians and as facilitators of participation and civic dialogue. This research will potentially be less applicable to the relationship between public affairs and society in other regions of the world, or in authoritarian states with low levels of interest group pluralism.